A Golden Rectangle Emerged!

Algebra Level 3

Find the value of x 4 x 3 6 x 2 + 9 x 4 { x }^{ 4 }{ -x }^{ 3 }-6{ x }^{ 2 }+9x-4 when x = 3 + 5 2 x=\frac { 3+\sqrt { 5 } }{ 2 }

This problem is part of the set Hard Equations

5 \sqrt { 5 } 3 + 5 3+\sqrt { 5 } 3 + 5 2 \frac { 3+\sqrt { 5 } }{ 2 } 3 + 2 5 3+2\sqrt { 5 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jan 17, 2015

If x = 3 + 5 2 x=\dfrac {3+\sqrt{5}}{2} , then it is the root of x 2 3 x + 1 = 0 x 2 = 3 x 1 x^2 - 3x +1 =0 \quad \Rightarrow x^2 = 3x -1

Therefore,

x 4 x 3 6 x 2 + 9 x 4 = ( 3 x 1 ) 2 x ( 3 x 1 ) 6 ( 3 x 1 ) + 9 x 4 x^4 - x^3 - 6x^2 + 9x -4 = (3x-1)^2 - x(3x-1) - 6(3x-1) + 9x - 4

= 9 x 2 6 x + 1 3 x 2 + x 18 x + 6 + 9 x 4 = 6 x 2 14 x + 3 = 9x^2 - 6x + 1 - 3x^2 + x - 18x + 6 + 9x - 4 = 6x^2 - 14x + 3

= 6 ( 3 x 1 ) 14 x + 3 = 18 x 6 14 x + 3 = 4 x 3 = 6(3x-1) - 14x + 3 = 18x - 6 - 14x + 3 = 4x - 3

= 4 ( 3 + 5 2 ) 3 = 6 + 2 5 3 = 3 + 2 5 = 4 \left( \dfrac {3+\sqrt{5}}{2} \right) - 3 =6 + 2\sqrt{5} - 3 = \boxed {3+2\sqrt{5}}

Prasun Biswas
Dec 17, 2014

Since I couldn't manage to factorize the given expression, I solved it in a much lengthy way. Take the value that we are about to find as S S and we will focus solely on the value at x = 3 + 5 2 x=\dfrac{3+\sqrt{5}}{2} . We have,

x = 3 + 5 2 ( 2 x 3 ) 2 = 5 4 x 2 12 x + 4 = 0 x 2 3 x + 1 = 0 x 4 3 x 3 + x 2 = 0 [Multiplying both sides by x 2 since x 0 ] x 4 = 3 x 3 x 2 x=\dfrac{3+\sqrt{5}}{2} \\ \implies (2x-3)^2=5 \\ \implies 4x^2-12x+4=0 \\ \implies \boxed{x^2-3x+1=0} \\ \implies x^4-3x^3+x^2=0 \quad \text{[Multiplying both sides by } x^2 \text{ since } x\neq 0\text{ ]} \\ \implies \boxed{x^4=3x^3-x^2}

Now, using these two results, we can reduce the degree of S and factorize it and further simplify as,

S = x 4 x 3 6 x 2 + 9 x 4 S = 3 x 3 x 2 x 3 6 x 2 + 9 x 4 S = 2 x 3 7 x 2 + 9 x 4 S = ( x 1 ) ( 2 x 2 5 x + 4 ) S = ( x 1 ) ( 2 ( x 2 3 x + 1 ) + ( x + 2 ) ) S = ( x 1 ) ( x + 2 ) S = x 2 + x 2 S = ( x 2 3 x + 1 ) + ( 4 x 3 ) S = 4 x 3 S=x^4-x^3-6x^2+9x-4 \\ \implies S=3x^3-x^2-x^3-6x^2+9x-4 \\ \implies S=2x^3-7x^2+9x-4 \\ \implies S=(x-1)(2x^2-5x+4) \\ \implies S=(x-1)(2(x^2-3x+1)+(x+2)) \\ \implies S=(x-1)(x+2) \\ \implies S=x^2+x-2 \\ \implies S=(x^2-3x+1)+(4x-3) \\ \implies \boxed{S=4x-3}

Now, S S has been simplified much and all you have to do is put the value of x x there and get the answer as 3 + 2 5 \boxed{3+2\sqrt{5}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...